Can't pay, won't pay : the case for economic disobedience and debt abolition - Taylor, Astra, editor; Recorded Books, Inc. (Chicago : Haymarket Books, 2020)
Debtors have been mocked, scolded and lied to for decades. We have been told that it is perfectly normal to go into debt to get medical care, to go to school, or even to pay for our own incarceration. We've been told there is no way to change an economy that pushes the majority of people into debt while a small minority hoard wealth and power.The coronavirus pandemic has revealed that mass indebtedness and extreme inequality are a political choice. In the early days of the crisis, elected officials drew up plans to spend trillions of dollars. The only question was: where would the money go and who would benefit from the bailout'The truth is that there has never been a lack of money for things like housing, education and health care. Millions of people never needed to be forced into debt for those things in the first place.Armed with this knowledge, a militant debtors movement has the potential to rewrite the contract and assure that no one has to mortgage their future to survive.Debtors of the world must unite. Through tactics such as strikes and collective bargaining, debtors' movements can help redress our country's foundations in racial capitalism and environmental destruction. As isolated individuals, debtors have little influence. But as a bloc, we can leverage our debts and devise new, powerful strategies to challenge the corporate creditor class and help win reparative, universal public goods.Individually, our debts overwhelm us. But together, our debts can make us powerful.
Title from resource description page (Recorded Books, viewed June 22, 2020).
eBooks on EBSCOhost
Keywords: Debt; Debt relief; Structural adjustment (Economic policy); Economic development; Human rights; Dettes; Ajustement structurel (Économie); Développement économique.; Droits de l'homme (Droit international); economic development; BUSINESS & ECONOMICS / Personal Finance / General; Structural adjustment (Economic policy); Human rights; Economic development; Debt relief; Debt; Business